PARTITION OF MEASURABLE SETS - Oduor, Owino Maurice; Olwamba, Otanga Levi; Omukunda, Aywa Shem (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
The theory of vector measure has attracted much interest among researchers in the recent past. Available results show that measurability concepts of the Lebesgue measure have been used to partition subsets of the real line into disjoint sets of nite measure. In this paper we partition measurable sets in â„œn for n â‰¥ 3 into disjoint sets of nite dimension.